COMPETENCIES FOR PHYSICAL EDUCATION TEACHERS - Pramann, Saowaluk; Kawjaratwilail, Toasak; Tanphanich, Theeranan (Journal of Liberal Arts and Management Science Kasetsart University, 2022)
With the changes in today's world, every aspect of life has to be adjusted, including education. Therefore, teachers who play an important role in driving education should continually have professional development to support the rapid changes in the education industry. In addition, teachers need to adjust and develop themselves to be more competent according to changes in today's world. Competency is the attribute that is the result from knowledge, skills, attitudes, and other behaviors. It could increase the ability to perform quality work and to achieve the higher required standards or goals. Competencies for physical education teachers refer to specific characteristics that are the results from knowledge, skills, abilities, attitudes, habits, and motivations of physical education teachers and reflect the teaching efficiency. They consisted of 7 competencies: 1) self and professional competence, 2) curriculum development competence, 3) learning management competence, 4) learner development competence, 5) innovation and research competency, 6) information technology competence, and 7) communication competence.